The Epidemiology of Trachoma in Darfur States and Khartoum State, Sudan: Results of 32 Population-Based Prevalence Surveys. (1st November 2016) - Elshafie, Balgesa Elkheir; Osman, Kamal Hashim; Macleod, Colin; Hassan, Awad; Bush, Simon; Dejene, Michael; Willis, Rebecca; Chu, Brian; Courtright, Paul; Solomon, Anthony W.
ABSTRACT: Purpose : To complete the baseline trachoma map of Sudan by estimating the prevalence of trachoma and associated risk factors in the five Darfur States and Khartoum State. Methods : Using a standardized methodology developed for the Global Trachoma Mapping Project, we undertook a cross sectional, community-based survey in each of 32 evaluation units (EUs) covering all accessible districts. Results : We enumerated a total of 84, 568 individuals, with 73, 489 people (86.9%) examined from 20, 242 households in 908 villages. The highest prevalence of trachomatous inflammation – follicular (TF) in children was found in El Fashir district (18.7%), and the lowest in El Malha district (0.0%). Five districts (El Fashir, Zalinji, Azoom, Maleet, and El Koma) were in the three EUs that had TF prevalences above the 10% threshold at which the World Health Organization recommends mass treatment with azithromycin, together with facial clean3liness and environmental improvement interventions, for at least 3 years. The highest trachomatous trichiasis prevalence in adults was found in the EU composed of Forbranga and Habillah (1.2%), and the lowest in the EU composed of As-salam and Belale districts in South Darfur (0.0%). TF in children was independently associated with younger age, unimproved sanitation in the household, having ≥5 children in the household, outside annual maximum temperatures <40°C, and living in an internally displaced persons camp. Conclusion : We found a high prevalence of trachoma in some areas of Darfur, but in general the prevalence throughout Darfur and Khartoum was low.